2022
DOI: 10.3390/su14074350
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Solvent Regeneration Technologies for CO2 Capture through Offshore Natural Gas Purification Processes

Abstract: It is estimated that 40% of natural gas reservoirs in the world are contaminated with acid gases (such as hydrogen sulfide and carbon dioxide), which hinder exploitation activities. The demand for natural gas will increase by 30% from 2020 to 2050, with the rise of industrial activities and the lifting of travel restrictions. The long-term production of these high acid-gas fields requires mitigation plans, which include carbon capture, utilization, and a storage process to reduce carbon emissions. Absorption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 109 publications
0
5
0
1
Order By: Relevance
“…Additionally, the high regeneration temperature requirement (e.g., 900 • C for hydroxide-based solvents) (Keith et al, 2018; National Academies of Sciences, 2019) poses a challenge in terms of thermal energy and heating rate efficacy; necessitating the need for alternative energy sources and the targeted delivery of energy (i.e., overcome reliance on bulk convective heating). In this context, electrical energy can be utilized to regenerate sorbents through techniques such as microwave (MW) and induction-based heating, which offer rapid dielectric heating rates compared to conventional thermal heating (Wilcox, 2020;Mohd Pauzi et al, 2022). Ozkan et al (2022) demonstrated that the use of electricity for both liquid and solid sorbent regeneration yields a lower thermal energy equivalent for DAC.…”
Section: Regeneration Energymentioning
confidence: 99%
“…Additionally, the high regeneration temperature requirement (e.g., 900 • C for hydroxide-based solvents) (Keith et al, 2018; National Academies of Sciences, 2019) poses a challenge in terms of thermal energy and heating rate efficacy; necessitating the need for alternative energy sources and the targeted delivery of energy (i.e., overcome reliance on bulk convective heating). In this context, electrical energy can be utilized to regenerate sorbents through techniques such as microwave (MW) and induction-based heating, which offer rapid dielectric heating rates compared to conventional thermal heating (Wilcox, 2020;Mohd Pauzi et al, 2022). Ozkan et al (2022) demonstrated that the use of electricity for both liquid and solid sorbent regeneration yields a lower thermal energy equivalent for DAC.…”
Section: Regeneration Energymentioning
confidence: 99%
“…CO 2 Absorption is a solvent-based method where CO 2 is captured using aqueous solutions, such as monoethanolamine (MEA), diamines and tertiary amines, aqueous ammonia, amino acid salts, ionic liquids, and deep eutectic solvents [42,43] CO 2 is captured when the gas stream containing the CO 2 is brought into contact with these solvents [44]. Some of these solvents absorb the CO 2 chemically, while others do it physically [45].…”
Section: Absorptionmentioning
confidence: 99%
“…However, these solvents have some drawbacks, such as high corrosion rates, high energy consumption, amine degradation, and a large footprint. To overcome these problems, the use of ionic liquids as solvents has been lately gaining attention due to inherent structure tunability, good affinity to CO 2 , and low volatility [44]. For CO 2 capture, the most mature and close to large-scale applications are absorption processes [43].…”
Section: Absorptionmentioning
confidence: 99%
“…Even though many different CCS technologies have been proposed to date, only a few have reached commercial status, highlighting CO 2 chemical absorption [5]. Currently, solvents such as ammonia, piperazine and amines have been proposed for their absorption of industrial CO 2 emissions, with commercial focus on the latter group [6,7]. Monoethanolamine (MEA) is one example of a commercial amine with a high capture capacity [8][9][10].…”
Section: Introductionmentioning
confidence: 99%